Comparative analysis between myocardial perfusion reserve and maximal ischemia score at single photon emission computed tomography with new-generation cadmium-zinc-telluride cameras - Nudi, Francesco; Biondi-Zoccai, Giuseppe; Nudi, Alessandro; Neri, Giandomenico; Procaccini, Enrica; Schilllaci, Orazio (Journal of nuclear cardiology, 2021)
Whether estimates of myocardial perfusion reserve (MPR) stemming from new-generation cadmium-zinc-telluride (CZT) cameras are accurate remains unclear. We queried our institutional database for patients undergoing MPR with CZT cameras. The primary goal was appraising the incremental diagnostic yield of MPR on top or at odds of maximal ischemia score (MIS). A total of 66 subjects were included. When distinguishing patients according to normal vs abnormal MPR (cut-off 2.1 mL/min/g) and normal vs abnormal MIS, 4 groups could be identified: 12 (18.1%) individuals with normal MPR and MIS, 12 (18.1%) with normal MPR and abnormal MIS, 16 (24.2%) with abnormal MPR and normal MIS, and 26 (39.4%) with abnormal MPR and MIS. MIS was significantly associated with several baseline features, whereas MPR did not. There was no significant association between MPR and MIS, nor with regional perfusion. Clinical outcomes were uncommon and not significantly associated with MPR or MIS, whereas angiographically significant coronary artery disease (CAD) was associated solely with MIS (P < 0.05), and not with MPR. There is limited agreement between CZT-derived MPR and baseline risk, perfusion and angiography results. Whether such discrepancies may still prove incrementally beneficial for the diagnosis or prognosis of CAD remains unclear.